Viral kinetics among persons living with HIV (PLWH) on Dolutegravir-based antiretroviral Regimen: A retrospective and prospective analysis from selected HIV clinics in Ghana. - Samuel Badu Nyarko; Joel Adu Twum; Aikins Sarpong Obeng; Helena Dede Djangba; Oksana Ryabinina; Foster Kyei; George Boateng Kyei; Nicholas Ekow Thomford (PLoS ONE)
Background Dolutegravir (DTG)-based antiretroviral therapy has demonstrated superior efficacy, tolerability, and durability when compared to other HIV treatment regimens. However, monitoring viral kinetics is critical for determining treatment efficacy and making sound judgments. The purpose of this study was to assess viral kinetics in people living with HIV (PLWH) on DTG-based ART and identify characteristics related to virologic response in the Cape Coast Metropolis, Ghana. Methods Among people living with HIV (PLWH) attending HIV clinics between January 2020 and December 2023, a prospective and retrospective analysis of viral kinetics and clinical data were carried out. Data on viral loads, clinical laboratory results, ART regimen, and sociodemographic data were gathered. Viral loads analysis was undertaken using the COBAS AmpliPrep/COBAS TaqMan HIV-1 test, v2.0. Univariate and multivariate analyses were carried out to assess the variables related to virologic response. Results Complete data was obtained for a total of 902 PLWH in this study. The average age was 45 ± 15.30 years, and 72.62% were female. The majority, 89.02% (835/902), had been on the DTG+3TC+TDF regimen. Over 60% had undetectable viral loads (<50 copies/mL). Univariate analysis shows a significant relationship between gender and virologic response, with females having a lower likelihood of virologic failure (OR: 0.60, 95% CI: 0.39-0.93, p-value = 0.024). In multivariate analysis, the duration of ART had various relationships with virologic response, with the odds ratio for two years reaching near significance (OR: 1.88, 95% CI: 0.98-3.59, p = 0.057). PLWH with viral loads >1000 copies/mL were 11.20% (101/902) while viral suppression, which was at detectable limits (>50 - ≤ 1000 cp/mL), was 13.08% (118/902) showing high rates of viral suppression. Conclusion The presence of virologic failures was of concern despite the high rates of viral suppression that DTG-based ART demonstrated. Undetectable viral suppression was higher than detectable viral suppression. Regular monitoring of viral kinetics, adherence, and comorbidities is essential to meeting the United Nations program on HIV/AIDS (UNAIDS) 95-95-95 targets and providing efficient therapeutic approaches for PLWH.